Kebijakan Bidang Ekonomi Pemda Kota Metro terhadap Pengelolaan Lokasi Usaha di Nuwo Intan Kota Metro Tahun 2018 - Viona Rahmawati Jubaidah; Rusnandari Retno Cahyani (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research discusses efforts to develop Metro City as a city of the future, focusing on the successful integration of the Trans Sumatra Toll Exit in Batanghari Ogan. In the context of development, emphasis is placed on the importance of green open space areas to make Metro City beautiful and act as a model for the autonomy of other cities. Through a literature review, relevant research includes analysis of regional economic regulations and the role of regional government policies in development, with examples of scientific journals that support business contributions to regional income. Although the results of previous research already exist, this research more specifically explores the economic policies of the Metro City regional government regarding the management of Nuwo Intan business locations in 2018. The nature of this research is descriptive and qualitative, using qualitative analysis to describe the phenomenon and influence of the Metro City Regional Government's economic policies on street vendors' income in Nuwo Intan.